Coconut Oil: From Diet to Therapy - Dayrit, Conrado S (Archīum Ateneo, 2017)
“Today, people are returning to natural diets in order to live healthier and happier lives—the hallmarks of ‘wellness’—and science has been validating the benefits. One of the natural foods being rediscovered is the coconut. Although vilified as a cause of heart disease, coconut oil has always shown itself to be a healthy and curative oil. Numerous studies using the tools of modern science are finally revealing—and validating—the beneficial effects of coconut oil.”—From the Prologue